Shareholders' Claim for Reflective Loss in International Investment Agreement through ISDS Arbitration Practice - Belaputri, Addyana; Agusman, Damos Dumoli; Amalia, Prita (University of Jember, 2023)
Shareholders’ claim for reflective loss appears to be commonly accepted by the Investor-State Dispute Settlement (ISDS) tribunals. Several international investment agreements (IIAs) have construed the condition of losses or damage under IIA to address the shareholder reflective loss (SRL) issue. Nonetheless, through the ISDS decision, the interpretation appears to be disparate. This article will aim to analyze the status of SRL in IIA through conditions of losses or damages as investment dispute characteristics and IIA text formulation to limit such conditions in addressing SRL issues through juridical normative and comparative study with a descriptive-analytical characteristic. Foreign direct investment regimes driven by the IIA show how important the IIA’s role is in providing adequate protection of investment including dispute mechanisms set through. The author will use the juridical and comparative methods by reviewing the existing statutory and case laws. The condition of loss or damage under IIA also appears to cover SRL. The limitation through the scope of allowed claims regarding whose losses, have been interpreted by several tribunals to limit a direct claim for SRL. However, the interpretation seems to be inconsistent with the other tribunals. An explicit text formulation and applying the loss-based general rule into IIA will then help to address consistent and genuine outputs of the applicable rule to limit the condition of losses or damage pertaining to the claim for SRL. In conclusion, the condition of losses or damage led the tribunal to allow the claim for SRL, yet through a limitation of the condition, the claim for SRL will be construed with specific requirements and procedures to avoid intersectoral issues. State parties in negotiating IIA are suggested to consider limiting the condition of losses or damage by adopting text formulation that led the ISDS tribunal’s interpretation to a genuine meaning of the applicability rule which the parties intended to, specifically, regarding investor’s right to claim SRL. Thus, the risk of harm that the host state suffers will be avoided.Keywords: Foreign Direct Investment, International Investment, International Law.